Response of Spodoptera litura Fab. (Lepidoptera: Noctuidae) larvae to Citrullus colocynthis L. (Cucurbitales: Cucurbitaceae) chemical constituents: Larval tolerance, food utilization and detoxifying enzyme activities. (January 2018) - Ponsankar, Athirstam; Vasantha-Srinivasan, Prabhakaran; Thanigaivel, Annamalai; Edwin, Edward-Sam; Selin-Rani, Selvaraj; Chellappandian, Muthiah; Senthil-Nathan, Sengottayan; Kalaivani, Kandaswamy; Mahendiran, Annamalai; Hunter, Wayne B.; Alessandro, Rocco T.; Duraipandiyan, Veeramuthu; et al.
Abstract: Pest management has increased the alarm across researchers because of the possible risk from harmful insecticides dispersed in the natural environment. Plant derivatives are established from plant extracts and displays latent effects against damaging pests in a multiple ways. Citrullus colocynthis (L.) Schrad, largely dispersed across the world in the warm area. A purified, fractionated ethyl acetate extract of C.colocynthis (bitter apple) has shown 90% lethality toward Spodoptera litura third instar larvae, and slightly lower lethality to the fourth and fifth instars. Based on the food utilization, the mechanism of lethality appears to be reduced digestive enzyme activity. The enzyme analysis of S. litura against fraction F5 demonstrated that the level of ACP, ALP, ATP and LDH decreased significantly based on their concentration. The gut histology of S. litura shows disturbance in the midgut columnar cells against the fraction F5 . The fraction F5 was further eluted using column chromatography and the subfraction A3 obtained and it was further characterized using FTIR and NMR. The subfraction A3 exhibits prominent mortality rate with 84% at 100 ppm concentration. The subfraction A3 was characterized and identified as stigmasterol. Highlights: Purified solvent extract of Citrullus colocynthis has shown toxicity against Spodoptera litura larvae. Survival, nutritional indices and gut enzymes of S. litura was negatively affected after treatment with C. colocynthis . The gut histology of S. litura shows disruption in the midgut columnar cells against treatment with C. colocynthis .